Not for Free at All Open Access Publishing and European Academia - Wessely, Christian (Journal for Religion, Film and Media)
The political demand that all results of university research be available through Open Access was a strategic decision that stakeholders have been required to embrace. However, Open Access is cost-free only for consumers, not for producers. Authors now need to not only produce excellent content but also secure financial support.Specific interest groups, in the interest of fair access to quality-assured publication, are establishing their own Open Access publication opportunities. This article sketches the emergence of the Open Access concept, its impact on the pressure to publish and career planning for young scholars, and the effort required to operate an Open Access journal (using the Journal of Religion, Film and Media as an example), focusing in particular on the workload associated with publishing one year’s output and the input/output relationship under current academic conditions.